Validação de vídeo educativo para equipe multidisciplinar sobre os direitos de idosos hospitalizados - Silva, Elânio Leandro da (2024)
Introduction: Population ageing is a worldwide phenomenon, especially in developing countries such as Brazil. In this context, the importance of legal provisions to ensure the rights of the elderly population is highlighted, given the physical, property and psychological limitations that come with human ageing. Objective: To validate an educational video for the multidisciplinary team on the rights of hospitalized elderly people. Methodology: This is a methodological study aimed at developing an educational video for the multidisciplinary team, developed in three stages: a scoping review; development of the educational video with script, narration and creation of illustrations; and validation of the storyboard. The literature was searched in the following databases: Lilacs, Medline, Scopus, Web of Science and Grey Literature. The terms used for the search were: Patient Rights; Aged; Hospitals, using the Boolean operator AND. The sample consisted of 8 articles that were classified and analyzed in three categories: the rights of the elderly; lack of knowledge of the elderly, companions and professionals; difficulties of organizational problems and challenges in the process of caring for the elderly. The empirical procedures, in which the content of the video was validated, involved the participation of 13 judges, all health professionals with experience in geriatrics, gerontology and care for the elderly. The video had 25 scenes that addressed the issue of the rights of the elderly in hospital and, finally, the third phase involved analytical procedures (checking the reliability of the info-product). The judges' assessment of the content was based on the CVI, making it possible to quantify the suitability of the video in relation to the seven aspects assessed, such as: objective, content, language, relevance, illustration, layout and motivation. Results: The multidisciplinary team's knowledge is still very limited. Despite recognizing the need, professionals do not know or respect the rights of the elderly. Ineffective communication, lack of autonomy, organizational structure and deficits in professional training stood out as the biggest challenges to quality care. This highlights the importance of creating tools for better professional training, in order to equip health professionals. With regard to the reliability of the product, the scores were above average for all the items assessed, indicating good quality in the content covered, with a final validation index of 0.90 confirming the relevance of the video's construction. Conclusion: The educational video is expected to achieve its main objective, which is to provide information as a form of training and guidance for the multidisciplinary team. It constitutes an effective and accessible alternative, seeking to ensure that the content is correctly transmitted and understood, contributing to the provision of quality care to elderly patients.